2015
DOI: 10.1124/dmd.115.064477
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of Gut Bacteria in the Metabolism of Deleobuvir: In Vitro and In Vivo Studies

Abstract: Deleobuvir is a potent inhibitor of the hepatitis C virus nonstructural protein 5B polymerase. In humans, deleobuvir underwent extensive reduction to form CD 6168. This metabolite was not formed in vitro in aerobic incubations with human liver microsomes or cytosol. Anaerobic incubations of deleobuvir with rat and human fecal homogenates produced CD 6168. Using these in vitro formation rates, a retrospective analysis was conducted to assess whether the fecal formation of CD 6168 could account for the in vivo l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…This topic is undertaken by McCabe et al (2015) in this issue; they used a combination of approaches to elucidate the impact of the gut bacteria on the metabolism of deleobuvir, a non-nucleoside polymerase inhibitor used to treat hepatitis C infections. This study also provides insights into the limitations and challenges associated with the use of in vivo and in vitro approaches to be used for studying the cometabolism of drugs in the host and gut microbiota.…”
Section: Impact Of the Gut Microbiome On The Metabolism And Pharmacokmentioning
confidence: 99%
“…This topic is undertaken by McCabe et al (2015) in this issue; they used a combination of approaches to elucidate the impact of the gut bacteria on the metabolism of deleobuvir, a non-nucleoside polymerase inhibitor used to treat hepatitis C infections. This study also provides insights into the limitations and challenges associated with the use of in vivo and in vitro approaches to be used for studying the cometabolism of drugs in the host and gut microbiota.…”
Section: Impact Of the Gut Microbiome On The Metabolism And Pharmacokmentioning
confidence: 99%
“…This method has the advantage of capturing a greater diversity of organisms and has been successfully applied to identify numerous drugs that are susceptible to microbial metabolism (Valerino et al, 1972;Caldwell and Hawksworth, 1973;Smith and Griffiths, 1974;Powis et al, 1979;Koch and Goldman, 1979;Koch et al, 1980;Lindenbaum et al, 1981;Elmer and Remmel, 1984;Harris et al, 1986;Strong et al, 1987;Shu et al, 1991;DH Kim et al, 1992;Lavrijsen et al, 1995;Watanabe et al, 1995;Kitamura et al, 1997;Sasaki et al, 1997;Basit and Lacey, 2001;Basit et al, 2002;Deng et al, 2011;Li et al, 2012;McCabe et al, 2015). However, when testing a community of microorganisms collectively, inter-strain antagonism may mask This article has not been copyedited and formatted.…”
Section: Mastering Microbial Metabolismmentioning
confidence: 99%
“…Adjusted geometric means (%gCV) for pharmacokinetic parameters and relative bioavailability of caffeine, tolbutamide, 4-OH tolbutamide, midazolam, and 4-OH midazolam in HCV-infected patients before (day 1) and after (day 9) treatment of 8 days with 600 mg TID deleobuvir (McCabe et al, 2015), and an acyl glucuronide of deleobuvir (deleobuvir-AG) were circulating at peak exposures of 59 and 32% of the parent deleobuvir, respectively. CD 6168 exposure is higher upon multiple dosing despite a short half-life , probably owing to the unique site of formation in the GI tract.…”
Section: Tablementioning
confidence: 99%
“…This distinction was made because the glucuronide metabolite is formed in the hepatocytes and thus portal vein concentrations were not expected to be higher than maximal plasma concentrations. Since CD 6168 is formed presystemically in the gastrointestinal tract by gut bacteria, it was regarded as administration of a second parent drug McCabe et al, 2015). The fraction absorbed for deleobuvir was considered to be 0.5, as an absorption, distribution, metabolism, and excretion (ADME) study showed ;50% of the radioactivity in feces was accounted for by CD 6168 and its metabolites .…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation